Corak Ghinâ’ dalam Membaca Alquran (Studi Historis terhadap Perkembangan Variasi Lagu Alquran Syaikh al-Qurrâ’ Azra’i Abdurrauf) - Wanto, Sugeng; Nasution, Muhammad Roihan; Tanjung, Hadi Gunawan (Al-I'jaz: Jurnal Kewahyuan Islam, 2020)
Fast traslateABSTRACTSheikh Azra'i Abdurrauf is Shaykh al-Qurrâ’ from North Sumatra who mastered the sciences of the Qur’an such as tajwîd, fashâhah, interpretation, qirâ'at and ghinâ'. However, his character and role is not seen in historical records and tends to disappear with his death. Therefore, the authors considers it important to write a study with the title "The Style of The Ghiná’ in Reading the Qur’an (Historical Study of the Development Variations the Qur’anic Song of Shaykh al-Qurrâ' Azra'i Abdurrauf)."The purpose of this research is to determine the style of the qur’anic song of Shaykh Azra'i Abdurrauf and the his role or progress of Syekh Azra'i Abdurrauf in the development of the qur’an in North Sumatra. In this research, the authors used the "Living Qur'ân" research method with sociological and phenomenological approaches. Icon translate     Fast traslate Icon translate     Fast traslate Icon translate